Produção social do espaço urbano e conflitos pela água na região metropolitana de são paulo - Fracalanza, Ana Paula [UNESP]; Campos, Valéria Nagy de O. (My University, 2006)
This paper analyses the social production of the urban space and the conflicts between the different water uses and users in the Metropolitan Region of Sao Paulo, since the end of the 19th century until nowadays.
Keywords: Conflicts; Urbanization; Water resources